Expression 23: "y" equals 7 left brace, 3 less than "x" less than 6 , right bracey=73<x<6
23
Expression 24: "y" equals 7 left brace, negative .4 less than "x" less than .5 , right bracey=7−.4<x<.5
24
Expression 25: "x" equals 6 left brace, negative 3 less than "y" less than 7 , right bracex=6−3<y<7
25
Expression 26: "y" equals 2 "x" minus 15 left brace, negative 5 less than "y" less than negative 3 , right bracey=2x−15−5<y<−3
26
Expression 27: "y" equals 2 "x" minus 11 left brace, negative 1 less than "y" less than 1 , right bracey=2x−11−1<y<1
27
Expression 28: "y" equals 2 "x" minus 9 left brace, 1 less than "y" less than 3 , right bracey=2x−91<y<3
28
Expression 29: "y" equals 7 left brace, 1 less than "x" less than 2.5 , right bracey=71<x<2.5
29
Expression 30: "y" equals 7 left brace, negative 2.4 less than "x" less than negative .9 , right bracey=7−2.4<x<−.9
30
Expression 31: 2 "x" plus negative 5 left brace, 5 less than "x" less than 6 , right brace2x+−55<x<6
31
Expression 32: "y" equals 2 "x" plus 7 left brace, 5.4 7 7 less than "y" less than 6.2 , right bracey=2x+75.477<y<6.2
32
Expression 33: "y" equals 2 "x" plus 7 left brace, 6.5 less than "y" less than 7 , right bracey=2x+76.5<y<7
33
Expression 34: "x" equals 1 left brace, negative 5 less than "y" less than negative 1 , right bracex=1−5<y<−1
34
Expression 35: "x" equals negative 1 left brace, negative 5 less than "y" less than negative 1 , right bracex=−1−5<y<−1
35
Expression 36: "y" equals 4 left brace, 2 less than "x" less than 4.2 , right bracey=42<x<4.2
36
Expression 37: "y" equals 3 left brace, 2 less than "x" less than 4.2 , right bracey=32<x<4.2
37
Expression 38: "x" equals 2 left brace, 3 less than "y" less than 4 , right bracex=23<y<4
38
Expression 39: "x" equals 4.2 left brace, 3 less than "y" less than 4 , right bracex=4.23<y<4
39
Expression 40: "x" equals 2.5 left brace, 3.7 less than "y" less than 3.9 , right bracex=2.53.7<y<3.9
40
Expression 41: "y" equals 3.9 left brace, 2.4 less than "x" less than 2.6 , right bracey=3.92.4<x<2.6
41
Expression 42: 5 left parenthesis, "x" minus 2.8 , right parenthesis squared plus 1.8 left parenthesis, "y" minus 3.8 , right parenthesis squared equals .0 35x−2.82+1.8y−3.82=.03
42
Hidden Label: left parenthesis, 3 , 3.9 , right parenthesis3,3.9
Label
43
Hidden Label: left parenthesis, 3 , 3.8 , right parenthesis3,3.8